Ball milled phosphorus modified biochar improved Nicotiana tabacum L. resistance against Phytophthora nicotianae: reducing oxidative damage, increasing defense hormone content and promoting phenylpropanoid metabolism - Ming, Chunlan; Zhang, Yushuai; Li, Mengze; Moussa, Mohamed G.; Liu, Tengfei; Wang, Hang; Ma, Yongfei; Huang, Wuxing; Xu, Zicheng; Xu, Jiayang; Jia, Wei (Frontiers in Microbiology, 2026)
IntroductionTobacco black shank (TBS), caused by Phytophthora nicotianae, poses a serious threat to tobacco production, highlighting the urgent need for sustainable management strategies. Meanwhile, tobacco stalk, a byproduct of tobacco cultivation, required effective recycling and value-added utilization.MethodsIn this study, four types of tobacco stalk derived biochar (unmodified biochar, H3PO4-modified biochar, ball-milled biochar, and ball-milled H3PO4-modified biochar) were prepared to evaluate their efficacy in controlling TBS. We evaluated physiological indices, including chlorophyll content, antioxidant enzyme activities, reactive oxygen species levels, and phytohormone profiles, along with changes in tobacco leaf metabolites, to explore the impact of modified biochar on diseased tobacco plants.ResultsThe ball milled-phosphorus modified biochar (BPT) exhibited a dense and uniform pore structure, markedly increased surface P content, and introduced abundant -OH and P-O functional groups, resulting in the most effective disease suppression. Soil application of BPT significantly reduced lesion length in infected plants, enhanced chlorophyll content, increased the activities of antioxidant enzymes [catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD)], decreased malondialdehyde (MDA), hydrogen peroxide (H2O2), and superoxide anion (O2−) levels. Moreover, BPT modulated phytohormone levels elevating indole-3-acetic acid (IAA), jasmonic acid (JA), abscisic acid (ABA), and salicylic acid (SA) and reshaped amino acid, lipid, and phenolic acid profiles. Metabolic pathway analysis indicated that BPT promoted phenylpropanoid as well as phenylalanine, tyrosine, and tryptophan biosynthesis, thereby strengthening tobacco resistance to P. nicotianae.DiscussionThis study elucidate the mechanisms underlying biochar-induced disease resistance and provide a promising approach for sustainable management of tobacco black shank using modified biochar.